Efektivitas antara Brisk Walk Exercise dan Relaksasi Otot Progresif terhadap Penurunan Kadar Gula Darah pada Diabetes Mellitus tipe 2 - Winda Yunita Miftahul Jannah; Nurul Hidayah; Agus Setyo Utomo (Jurnal Keperawatan Terapan, 2019)
Blood sugar levels in patients with diabetes mellitus type 2 can be reduced with walk-through brisk therapy and progressive muscle relaxation. This is because when walking exercise is done regularly can stimulate glycogen synthesis through increased action of insulin and stimulate glucose transport by GLUT4 glucose transporer. Meanwhile, when progressive muscle relaxation is done regularly able to inhibit the pathor stressor thus reinforcing the positive attitude to stress stimulation and resulted in reduced hypothalamus. This study aims to determine the effectiveness between Brisk Walk Exercise and Progressive Muscle Relaxation on the decrease of blood glucose level in Diabetes Mellitus Type 2. The design of this study used Quasy Experimental with Pre test and Post Test Group Design with consecutive sampling. The sample consists of 30 respondents, divided into 2 groups: Brisk Walk Exercise group and Progressive Muscle Relaxation group. The result of Paired T test of Brisk Walk Exercise was obtained p is 0,000, this means that there is a significant difference. While in the Progressive Muscle Relaxation group the p is 0.000, this means there is a significant difference. In Paired T test, p is 0,000, means that there is significant difference between Brisk Walk Exercise and Progressive Muscle Relaxation. Nurses are expected to apply non pharmacological therapy such as Brisk Walk Exercise and Progressive Muscle Relaxation as an alternative therapy an easy patient choice to do to lower blood sugar levels.